Developing Social Competence of Physiotherapy Students During Workshops Using Active Teaching Methods: An Experimental Study - Femiak Joanna; Czechowski Marcin (Sciendo, 2023)
Objective: The objective of this study was to answer the questions: 1) will the use of active methods in teaching workshops lead to an increase in indices of social competence in students? 2) do workshops conducted with active methods affect the development of social competence of women and men to the same extent? Methods: A pedagogical experiment with 140 first-year students (age: 18-26 years, with a mean age of 20.7 (SD 0.96) of the Faculty of Rehabilitation. The experimental group practised social skills using active methods. The control group studied the same content without active methods - based on text reading and analysis. We used the psychometric Social Competence Test, which has 3 parts: assertiveness, intimacy, and social exposure, and an overall index on a scale of 1 to 4. Result: Participation in the classes resulted in an increase in the subjects' indices of competence for assertiveness (η2= 0.13), intimacy (η2=0.07), social exposure (η2=0.06), and overall index (η2=0.12). Changes in indices of the competencies studied in the experimental and control groups were at a similar level, with a small effect (η2=0.01). There was a small interaction effect for gender and workshop participation (η2=0.01). Conclusion: Active methods used in teaching classes did not result in an increase in social competence indices in first-year physiotherapy students. The gender of the respondents was irrelevant to the effectiveness of the development of social skills in workshop classes; therefore, the content and methods of working with women and men should be the same.